Penerapan Media Pop-Up Book Untuk Meningkatkan Pemahaman Materi Fotosintesis Peserta Didik Kelas VIII Mts DDI Wanio - Andika, Andika; Usman; Novia Anugra (Program Studi Tadris IPA IAIN Parepare, 2025)
The research aimed to determine the application of pop-up books in the learning of eighth-grade students at MTs DDI Wanio, to determine students' understanding of photosynthesis before the application of pop-up books, and to determine the increase in students' understanding of photosynthesis after the application of pop-up books.This study used Classroom Action Research (CAR). Quantitative analysis techniques were used to analyze test scores on photosynthesis, including percentage averages, secondary deviations, and graphs. Qualitative analysis techniques were used to analyze observational data, summarizing and describing the research results through observations. Learning outcomes in cycles I and II improved compared to the pre-action period, as demonstrated by the average class score, which rose from 39 to 93.The percentage of students achieving the Minimum Competency (KKM) > 75 also increased from 38.5% to 93%. This data demonstrates that the use of pop-up books is effective when applied to photosynthesis learning. Students are more active and engaged in learning, and they also experience learning without always requiring technology. The data obtained in cycle II demonstrated that the research met the criteria for success, as the use of pop-up books was successful, as indicated by the percentage of students who passed the KKM > 75, thus eliminating the need for further research.